Assessing seismic resilience of school educational sector. An attempt to establish the initial conditions in Calabria Region, southern Italy. (December 2020) - Fontana, Cora; Cianci, Eleonora; Moscatelli, Massimiliano
Abstract: School education constitutes one of the strategic functions to be recovered after an earthquake. The structural improvement of school buildings together with the strengthening of the administrators' capacity to react positively following an earthquake are key factors that contribute to social vulnerability's reduction. Nevertheless, in Italy, the issue of risk reduction policies related to school sector is not yet consolidated in the institutional agendas. Observing the last major Italian earthquakes what remains predominant is school buildings' damage degree with consequent interruption of the system functionality. Among the causes: the building heritage vulnerability and the lack of risk mitigation policies, capable of building a resilient community for future earthquakes. That of resilience is considered a relevant paradigm to address the issue of how to strengthen the school sector's capacity to ensure the buildings physical safety and to guarantee the maintenance of the school function, looking at pre and post-event phases. The paper proposes a set of indicators and a methodology for a preliminary assessment of the educational sector's seismic resilience, in terms of initial conditions. The method has been tested on a first case study: Calabria Region, Southern Italy. The results show that spatial differences in the educational sector's seismic resilience are evident. Except for some large urban areas, the less resilient areas are grouped mainly in the southern part of the Region, while the most resilient ones are located mostly in the central-northern sector. The ambition is to identify a repeatable approach, useful as guidelines for school seismic prevention policies.